Application of heuristic algorithms in warehouse order picking routes - Purwanto, Cipto; Oktarina, Rienna (Universitas Sultan Ageng Tirtayasa, 2024)
Order picking is a costly activity in warehouse operations, accounting for up to 65% of total warehouse operational costs. This study aims to improve the efficiency and productivity of the order picking process in a warehouse by applying two heuristic methods, namely the S-Shape and aisle-by-aisle approaches. Data were processed using InterActive Freight & Warehouse software, which is designed for warehousing and logistics management with interactive features that assist in optimizing order picking routes. The software employs heuristic methods, such as the S-Shape and aisle-by-aisle strategies, to reduce the distance workers travel to pick goods. The results show that the S-Shape method significantly reduces workers' travel distance compared to other methods. Thus, the application of heuristic methods in optimizing order picking routes proves effective in enhancing warehouse operational efficiency. The S-Shape method yields an average total distance traveled of 678.729 meters, while the aisle-by-aisle method results in 684.04 meters. Additionally, the S-Shape method increases line order productivity from 30 lines of orders per packing list to 84 lines of orders per packing list, with a cycle time of 45.25 seconds to complete the picking process for one line of orders.